Insight into the molecular interaction between the cyclic nucleotide-binding homology domain and the eag domain of the hERG channel - Li, Qingxin (2016)
The gating of the hERG channel is regulated by its eag domain through molecular interaction with either the cyclic nucleotide-binding homology domain (CNBHD) or the linker between transmembrane segments 4 and 5. Our NMR study on the purified CNBHD demonstrated that it contains nine β-strands and does not bind cAMP. We show that the eag domain binds to the CBND through an interface containing several disease-associated mutations. The N-terminal cap domain and R56 in the eag domain are important for the interaction with the CNBHD. Residues from the CNBHD that were affected by the interaction with the eag domain were also identified. A R56Q mutation does not cause major structural changes in the eag domain and showed reduced interaction with the CNBHD.